Genetic diversity within local and introduced cultivars of wheat (Triticum aestivum L.) grown under Mediterranean environment as revealed by AFLP markers - Arabi, Mohammed Imad Eddin; Shoaib, Amina; Al-Shehadah, Eyad; Jawhar, Mohammed (Acta Biologica Szegediensis, 2019)
Information on genetic diversity among cultivars is critical in wheat improvement. In this work, heterogeneity within local and introduced cultivars of bread wheat grown in Syria was investigated using amplified fragment length polymorphism (AFLP) markers. The eight primer pairs were used to detect 177 polymorphic bands among the 21 cultivars resulting in an average of 22.13 (57.3%) polymorphic loci per primer pair. Major allelic frequency ranged from 0.50 to 0.75 with a mean 0.64, and estimated gene diversity was 0.45. Values of average polymorphic information content (PIC) for these markers were estimated to be 0.34. This low value might be attributed to the rigorous selection pressure aimed at cultivar purity and associated breeding practices. Dissimilarity values ranged from 0.32 to 0.66 with an average of 0.54, indicating that such techniques sample distinct genome regions. Three major subgroups of wheat cultivars were identified using the unweighted pair-group method with arithmetic means analysis (UPGMA), with all local cultivars falling into one cluster, which was confirmed by a principal component analysis (PCA). The narrow genetic diversity observed among Syrian wheat cultivars suggests the need of broadening the genetic base of wheat breeding materials, including local landraces.